2019
DOI: 10.1016/j.visres.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flash suppression operates in local spatial zones: Effects of mask size and contrast

Abstract: Continuous flash suppression (CFS) is a technique in which presenting one eye with a dynamic Mondrian sequence prevents a low-contrast target in the other eye from being perceived for many seconds. Frequently used to study unconscious visual processing, CFS bears many similarities with binocular rivalry (BR), another popular dichoptic stimulation technique. It is therefore puzzling that the effect of mask size and contrast seem to differ between CFS and BR. To resolve this discrepancy, we conducted a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…For example, presumed unaware processing has been identi ed for faces and facial expressions (Webb & Hibbard, 2020;Yang et al, 2007), simple geometric features, such as closure (Meng et al, 2012; and animacy (Sun et al, 2022;Zhu, Drewes, Peat eld, et al, 2016). While it has been shown that the properties of the masks in uence suppression effectiveness in multiple ways (Drewes et al, 2018(Drewes et al, , 2020Han et al, 2016Han et al, , 2019, in many cases, the masks used in the relevant studies were treated as independent of the targets, or at least were not designed with speci c targets in mind (Drewes et al, 2023;Pournaghdali & Schwartz, 2020). Only few studies directly investigated mask design with respect to the target stimuli (Drewes et al, 2023;Han et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, presumed unaware processing has been identi ed for faces and facial expressions (Webb & Hibbard, 2020;Yang et al, 2007), simple geometric features, such as closure (Meng et al, 2012; and animacy (Sun et al, 2022;Zhu, Drewes, Peat eld, et al, 2016). While it has been shown that the properties of the masks in uence suppression effectiveness in multiple ways (Drewes et al, 2018(Drewes et al, , 2020Han et al, 2016Han et al, , 2019, in many cases, the masks used in the relevant studies were treated as independent of the targets, or at least were not designed with speci c targets in mind (Drewes et al, 2023;Pournaghdali & Schwartz, 2020). Only few studies directly investigated mask design with respect to the target stimuli (Drewes et al, 2023;Han et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation of different kinds of random noise for CFS masking found that spatial pink noise (1/F noise) achieved the longest suppression duration compared to other random noises 29 . Other features and specially constructed masks have also received some recent attention [30][31][32] . Contrary to this, the direct relationships between masks and targets have received very little if any attention, even though in binocular rivalry 33,34 interactions in suppression (or dominance) duration between rivaling stimuli are well documented [35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…In vision, cooperative and inhibitory interactions among neighbouring spatial zones have been observed in both binocular 29 , 30 and dichoptic viewing conditions 31 36 . This raises two questions: (1) whether or not the DE is a retinotopic effect that only affects stimuli presented to deprived retinal locations, and (2) if local DEs interact with neighbouring spatial zones.…”
Section: Introductionmentioning
confidence: 99%